2004
DOI: 10.1111/j.1432-1033.2004.04189.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxidase inhibition by insulin in the bovine thyroid cell proliferation mechanism

Abstract: Monolayer primary cultures of thyroid cells produce, in the presence of insulin, a cytosolic inhibitor of thyroid peroxidase (TPO), lacto peroxidase (LPO), horseradish peroxidase (HRPO) and glutathione peroxidase (GPX). The inhibitor, localized in the cytosol, is thermostable and hydrophylic. Its molecular mass is less than 2 kDa. The inhibitory activity, resistant to proteolytic and nucleolytic enzymes, disappears with sodium metaperiodate treatment, as an oxidant of carbohydrates, supporting its oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In diabetes, the main sources of ROS generation in the vasculature include glucose auto-oxidation, the polyol pathway, AGE, mitochondrial electron transport chain (ETC), uncoupled eNOS, and NAd (P)H oxidases, with the latter enzymes arguably a major source of ROS generation in hypertension, atherosclerosis, and diabetes [26,29]. Recently, insulin has been reported to increase intracellular ROS production, possibly through phosphatidylinositol 3´-kinase-dependent mechanism and protein kinase C-dependent mechanism [5][6][7][8][9]. Our study demonstrated that insulin could increase intracellular ROS production in BRECs also through mitochondria and NADPH oxidase, as administration of NAd (P)H inhibitor apocynin can counteract insulin-induced overproduction of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diabetes, the main sources of ROS generation in the vasculature include glucose auto-oxidation, the polyol pathway, AGE, mitochondrial electron transport chain (ETC), uncoupled eNOS, and NAd (P)H oxidases, with the latter enzymes arguably a major source of ROS generation in hypertension, atherosclerosis, and diabetes [26,29]. Recently, insulin has been reported to increase intracellular ROS production, possibly through phosphatidylinositol 3´-kinase-dependent mechanism and protein kinase C-dependent mechanism [5][6][7][8][9]. Our study demonstrated that insulin could increase intracellular ROS production in BRECs also through mitochondria and NADPH oxidase, as administration of NAd (P)H inhibitor apocynin can counteract insulin-induced overproduction of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been reported for the phenomenon: first, diabetes was severe at the early stage; however, randomized clinical trails have ruled out this possibility [4]; second, insulin reduced retinal blood flow and subsequently led to retinal hypoxia, increased vascular permeability, and edema; third, insulin could cause arthrosclerosis and promote mitosis, thrombosis formation; finally, vascular endothelial growth factor was also thought to be involved in insulin-induced deterioration of retinopathy. Recently, insulin has been reported to increase intracellular reactive oxygen species (ROS) production in HepG2 cells [5], 3T3L1 adipocytes [6], thyroid cells [7], and human fibroblasts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This increase in ROOH levels could be because of a higher production or lower activity of degrading enzymes (that is, CAT) or to a combination of both events. Preliminary results demonstrated that an unspecific inhibitor of peroxidases 34 was increased in the cytosolic compartment of hIFNb-expressing EW7 cells (data not shown). On the other hand, we found that hIFNb gene decreased the antioxidant capacity of EW7 cells (Figure 7d).…”
Section: Resultsmentioning
confidence: 92%
“…ever, conversely, the mechanism of the production of IPGP from the membrane ' s GPI is not clear [6] . To date, the exact chemical structure of IPGs has not been elucidated and they are identifi ed by the methods reported by Krawiec et al [7] . The peroxidase inhibitor is termed an IPG-like product, considering its individual components.…”
Section: Inhibition Of Peroxidase and Catalase Activities And Modulatmentioning
confidence: 99%
“…The peroxidase inhibitor is termed an IPG-like product, considering its individual components. Krawiec et al [7] showed that insulin ' s promotion of thyroid cell proliferation may be attributed to the inhibition exerted by IPG on GPX and TPO activities. This inhibition enhances the H 2 O 2 level, which would be the signal for the induction of the mitogenic mechanism, acting on the oncogene c-jun, as was demonstrated by Lee et al [8] .…”
Section: Inhibition Of Peroxidase and Catalase Activities And Modulatmentioning
confidence: 99%